SOCIAL CAPITAL AND ITS INFLUENCE ON RURAL CREDIT MARKET - Fernando Perrini Daruge; Roberto Arruda De Souza Lima (European Regional Science Association (ERSA), 2010)
This study analyses the relationship between social capital accumulation and the amount of rural credit market contracts of the State of S\~ao Paulo, Brazil. The most important definitions of social capital found on literature and the main ways of creation and measure this variable were reported. It discusses the connection between social capital and information and how this relation contributes to the reduction of financial intermediation's transaction costs, that results on rural credit volume increasing. It was used the same logit regression model that have been created and used by LIMA (2003), to empirically test the effect of social capital on the volume of rural credit. The data, from the municipalities of the State of S\~ao Paulo, are from 2007/2008 official statistics (Farm Census, LUPA and SEADE's data basis). The results indicate that the level of social capital is positively-correlated with the amount of rural credit. That shows the governmental incentives to further increase and maintain social capital would result on rural sector's development.
Keywords: Z13; Q14; G14; L14; H81; 330; social capital; rural credit; logit